The Influence of Green Credit on the Commercial Banks’ Financial Performance: Evidence from China - Zhang, Ruiping (2022)
This study examines the impact of green credit on commercial banks’ financial performance in China, factoring in both profits and risk respectively. The development of the green economy has brought about emergent green credit market since the government became determined to address environmental issues. Both environmental management and the green production method innovation require substantial financial support, and green credit from bank is their main source. The main purpose of this study is to explore whether there is a correlation among the unfolding of green credit business, the profitability of banks and the credit risk of loans. The study in this paper selects 19 Chinese listed banks and collects 9 years of panel data covering the period from 2013 to 2021. Two robust standard error fixed-effects panel regression models based on the principle of linear estimates are established. The empirical results show that when the proportion of green credit (as a percentage of total credit) increases, it brings about a decrease in ROA, slightly hurting the profits of commercial banks in China. But as the green credit expands, the NPL of unwanted loans decreases, moderating the risk faced by banks and optimising asset quality. And the model results are significant. The paper concludes that the promotion of green credit has temporarily been a hindrance to banks' earning and the long-term impact is unclear so far. And green credit is less likely to default and therefore lower the non-performing ratio of banks. Chinese commercial banks are still relatively passive in the development of green credit. There are still some imperfections in the implementation of China's green credit policy, which, if updated and improved, would have a more significant benefits to banks in the future. This study contributes to the literature on the correlation between green credits and banks' financial performance, supplement the empirical case in the area of green credit. Additionally, it serves as a resource and reference for future government policymaking and bank development.